25 Years of Operation of the ‟Santa María De Loreto” Photovoltaic Plant, Cuba - José Emilio Camejo Cuán; Rubén Ramos Heredia; Roger Proenza Yero; José Felipe Vigil (Newinera Publisher, 2022)
The work addresses the main socio-technological aspects of the electrification process with photovoltaic solar technology , during 25 years of exploitation, in the rural community